Produção de feijão caupi (Vigna unguiculata (L.) Walp) através da infiltração subsuperficial de esgoto doméstico em solo arenoso - Lima, Paulo César Cunha (2005)
The production of cowpea beans (Vigna unguiculata (L.) Walp.) was evaluated in a real scale in this research project, by using the disposal of domestic sewage into the soil through the sub-superficial infiltration. The research was carried out during two periods. The first one was in the rainy season from January to April, and the second one in the dry season from August to November, 2004. The physical structure of the experimental station was built at the Horticulture Sector of the Agrarian Sciences Center, on the Pici Campus of the Federal University of Ceará, Fortaleza – CE, and was composed of six masonry seedbeds made of ceramic bricks with the following dimensions: 11m long, 1m wide, 0,60m deep, and 1% slant. The seedbeds were waterproofed with a black plastic blanket of 250 μ. The soil material used for the filling of the seedbeds was removed from a nearby area located by the place of the experiment. For comparative analysis, the six seedbeds were divided into two groups of three each. The first one was irrigated with underground water pumped from a deep well located in the place of the experiment, and the second one was irrigated with domestic sewage pumped from the sewage collecting pipe, which goes through the Pici Campus. The water volume used in the irrigation of the seedbeds was of 0,70 m³/day. The seedbeds were still divided into 2m sectors in order to better to evaluate the production along the seedbeds. The production was evaluated through the counting of the number of seeds and pods, and the productivity was assessed by the weight of seeds per useful area of 10,00m² located in each seedbed. In the rainy season, the seedbeds irrigated with domestic sewage presented average seed production data of 248,52 Kg ha-1, and the ones irrigated with raw water showed an average production of 1.377,52 Kg ha-1. The average productivity of grains in the dry season was of 767,08 Kg.ha-1 in the seedbeds irrigated with domestic sewage, and 757,43 Kg.ha-1 in the ones irrigated with water. The domestic sewage, despite being an alternative source of water and nutrients for the plants, cares regarding the agricultural handling should be considered to avoid risks to the environment and the health of the population. It was concluded, therefore, that the disposal of domestic sewage into the soil through the sub-superficial infiltration contributed to a larger production of cowpea beans, which makes this practice advisable in small rural communities, mainly in the semi-arid region of the Brazilian northeast